2021
DOI: 10.1523/eneuro.0184-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Input-Independent Homeostasis of Developing Thalamocortical Activity

Abstract: The isocortex of all mammals studied to date shows a progressive increase in the amount and continuity of background activity during early development. In humans the transition from a discontinuous (mostly silent, intermittently bursting) cortex to one that is continuously active is complete soon after birth and is a critical prognostic indicator. In the visual cortex of rodents this switch from discontinuous to continuous background activity occurs during the two days before eye-opening, driven by activity ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…As expected ( Dooley et al, 2021 ; Glanz et al, 2021 ; Gómez et al, 2021 ), pups spent more time in AS than wake at P8 (AS: 57.7 ± 2.5%; wake: 30.9 ± 1.9%) and P12 (AS: 44.0 ± 3.6%; wake: 39.3 ± 3.5%). Also, the transition from discontinuous cortical activity at P8 to continuous activity at P12 was evident in all three areas, as described previously in primary somatosensory, motor, and visual cortex ( Golshani et al, 2009 ; Rochefort et al, 2009 ; van der Bourg et al, 2017 ; Glanz et al, 2021 ; Riyahi et al, 2021 ).…”
Section: Resultssupporting
confidence: 83%
“…As expected ( Dooley et al, 2021 ; Glanz et al, 2021 ; Gómez et al, 2021 ), pups spent more time in AS than wake at P8 (AS: 57.7 ± 2.5%; wake: 30.9 ± 1.9%) and P12 (AS: 44.0 ± 3.6%; wake: 39.3 ± 3.5%). Also, the transition from discontinuous cortical activity at P8 to continuous activity at P12 was evident in all three areas, as described previously in primary somatosensory, motor, and visual cortex ( Golshani et al, 2009 ; Rochefort et al, 2009 ; van der Bourg et al, 2017 ; Glanz et al, 2021 ; Riyahi et al, 2021 ).…”
Section: Resultssupporting
confidence: 83%
“…Our results indicate however that homeostatic set-points can be altered by the profound changes in excitatory and inhibitory circuits resulting from visual deprivation (Ribic, 2020). While enucleation at P6--when spontaneous firing rates are 10% of adults (Riyahi et al, 2021)--did not significantly change adult firing rates, binocular deprivation–a procedure that causes less acute reduction in firing-rates and allows for greater homeostatic plasticity in adults (Hengen et al, 2013; Keck et al, 2013)--did lower firing-rates, but only during Stationary periods. It is unclear whether mean firing-rates were truly lower in sutured animals and an increased movement-related signal normalized them, or whether the firing-rate set points are similar in both animals but set during the movement period.…”
Section: Discussionmentioning
confidence: 95%
“…Here we examined the effect of two forms of early-life blindness on the establishment and maintenance of cortical dynamics. Bilateral enucleation at P6 or P13 allows us to compare the effect of retinal input removal before and after the onset of mature dynamics (Riyahi et al, 2021), without the significant thalamic and cortical rewiring caused by earlier loss of retinal inputs in mice (Olavarria and Hiroi, 2003; Golding et al, 2014). Binocular eyelid suture initiated before eye-opening deprives the animal of pattern vision and the ability to guide behavior visually, while preserving luminance detection and circadian rhythms (Kampf-Lassin et al, 2011), similar to bilateral cataracts.…”
Section: Introductionmentioning
confidence: 99%
“…We found that PCA of model parameters could be useful for qualitative assessment of EMO quality and heterogeneity of obtained models. Second, to set the strength of retinal inputs, we used the firing rate of TC neurons observed in vivo and ‘functionally’ estimated synaptic conductance at this age by assuming that total synaptic conductance is subject to homeostatic regulation and firing rate is the target activity parameter ( Riyahi et al, 2021 ). Using homeostatic regulation to set synaptic conductance is critical for modeling heterogeneous networks, where a single value for synaptic conductance would not work for all neurons.…”
Section: Discussionmentioning
confidence: 99%